Implementação de um algoritmo evolutivo utilizando a representação nó-profundidade-grau no processador Nios II do FPGA - Vinhal, Gustavo Siqueira (2013)
Many relevant problems to NP-Hard class are present in the real world. Among them we can mention the problems of network design (PNDs) that involve electricity distribution, vehicle traffic, and others. There are not algorithms which provide a exact solution for these types of problems with an acceptable computation time. Over the years, research has been developed used evolutionary algorithms (EAs) to provide an efficient solution with a acceptable computation time for these problems. In addition, appropriate data structures may further improve the performance of EAs to PNDs. The node-depth-degree (NDDE) representation have show significant results for PNDs. The application of EAs in hardware can improve the performance of the algorithm. In this sense, this work presents the implementation of a EA in Nios II processor of a FPGA board to solving the PND minimum spanning tree with degree constraint. The results demonstrate that the implementation of EAs in hardware brings significant results with better performance, due to the power of parallelism present in the FPGA.